Community Social Impact Analysis of Kelan Green Beach Tourism Development: (PT Pertamina Patra Niaga DPPU Ngurah Rai CSR Program) - Sabrina, Inggar Mayang; Hartato, Muhammad; Ahmad, Yusnur Rainday; Arifin, Muhson; E.A.A, Putri Kinasih (Indonesian Journal of Social Responsibility Review (IJSRR), 2022)
This research was conducted to analyze the impact of the development activities of Kelan Beach tourism arrangement by Pokdarwis which is a fostered group of PT Pertamina Patra Niaga DPPU Ngurah Rai. The location of this research was conducted in Kelan Traditional Village, Tuban Village, Kuta District, Badung Regency, Bali. The method used in this research is descriptive qualitative research using a behavioristic theory approach. The conclusion of this research is that PT Pertamina Patra Niaga's DPPU Ngurah Rai CSR activities through Green Beach Kelan activities have several measurable impacts. This can be seen based on the analysis of the sustainability compass in the form of the impact from the nature side in the form of processing 1500 kg of sea wood waste, from the economic side, income from tourism is IDR 27,000,000 on average per month, from the social side, 17 group members have increased skills in management of tourism management, and in terms of well being 17 group members have the ability to process marine wood waste. This Kelan Green Beach development activity is one of the innovations in developing coastal tourism in the Badung Regency, Bali.